2015
DOI: 10.1002/jsfa.7058
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of kokumi peptide from yeast extract by LC-Q-TOF-MS/MS and sensomics approach

Abstract: Key kokumi-active fractions were purified from yeast extract. Among them, ten important kokumi peptides from yeast extract were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 30 publications
4
67
1
Order By: Relevance
“…Some researchers reported that Phe‐Ala‐Leu‐Pro‐Glu‐Tyr‐Leu‐Lys had a bitter taste (Masuda & Kitabatake, ), and other researchers found that Ala‐Pro‐Pro‐Pro‐Pro‐Ala‐Glu‐Val‐His‐Glu‐Val‐Val‐Glu showed a sour taste (Okumura et al ., ). The results of the sensory evaluation indicated that the thickness taste of the chicken peptides might be attributed to synergy with other flavour molecules in the food, and that the thickness taste was perhaps produced by increasing the intensity of the umami or salty tastes (Liu et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers reported that Phe‐Ala‐Leu‐Pro‐Glu‐Tyr‐Leu‐Lys had a bitter taste (Masuda & Kitabatake, ), and other researchers found that Ala‐Pro‐Pro‐Pro‐Pro‐Ala‐Glu‐Val‐His‐Glu‐Val‐Val‐Glu showed a sour taste (Okumura et al ., ). The results of the sensory evaluation indicated that the thickness taste of the chicken peptides might be attributed to synergy with other flavour molecules in the food, and that the thickness taste was perhaps produced by increasing the intensity of the umami or salty tastes (Liu et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Each sample was given a score between 1 and 10 as follows: 0, not detectable; and 10, strongly detectable (Han et al, 2017). For a period of more than 3 months, the panelists were trained daily to recognise the taste characteristics, in which the following taste models were evaluated: 50 mmol L À1 sucrose for sweet taste; 20 mmol L À1 citric acid for sour taste; 1 mmol L À1 caffeine for bitter taste; 10 mmol L À1 monosodium glutamate (MSG) for umami taste; and 10 mmol L À1 glutathione (GSH) for kokumi taste (Liu et al, 2015). Sensory evaluation criteria are shown in Table 1.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…The peptides were dissolved in distilled water at 10 mmol L −1 as a first step, according to Liu et al . 's instructions . The sensory evaluation results showed that, among that four peptides, Pro‐Leu (4) could only impart bitterness, while other three bitter peptides had sour, kokumi and / or astringent tastes along with the bitterness.…”
Section: Resultsmentioning
confidence: 99%
“…The taste threshold was determined by synthesized model peptides tests: synthesized peptides were dissolved in distilled water, which was adjusted to pH 5.7 with ascending concentrations of the stimulus following the procedure reported previously . The taste threshold for bitter amino acids was from the previous study . The taste threshold determination was conducted in the same way as the TDA.…”
Section: Taste Profile Analysismentioning
confidence: 99%